The relation between sleep habits, fatigue, impact on family and quality of life in children with first-time cancer and recurrent cancer - Numanoğlu-Akbaş, Ayşe; Yakut, Hatice; Erdan-Kocamaz, Deniz (İnönü Üniversitesi Tıp Fakültesi, 2019)
Aim: This study was planned to determine the conditions related to sleep, fatigue, and impact on family in children with Acutelymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) who had cancer for the first time and children who had recurrentcancer.Material and Methods: The study included 74 children (41 girls, 33 boys) with a mean age of 8.11 ± 3.77 years. Children evaluatedwith child and parent report of Pediatric Quality of Life “and PedsQL Healthcare Satisfaction Generic Module” should be aded.Inventory (PedsQL) Cancer Module, Children’s Sleep Habits Questionnaire (CSHQ), Borg Scale and Impact on Family Scale (IPFAM).Results: There was a statistically significant difference, in terms of PedsQL parent report total score (p=0.003), between the childrenwho had cancer for the first time and children who had recurrence cancer, and the values of latter were higher. A positive correlationwas found between the PedsQL child and parent report scores for all children with cancer (p= 0.000).Conclusion: According to the results of our study, it was seen that children who have recurrent cancer had reported a better qualityof life and that children and parents have similar perceptions in terms of quality of life.
Keywords: çocuk; kanser; yaşam